2014
DOI: 10.1142/s0217732314500709
|View full text |Cite
|
Sign up to set email alerts
|

Observing the inhomogeneity in the holographic models of superconductors

Abstract: We study the gravity duals of striped holographic superconductors in the AdS black hole and AdS soliton backgrounds. We show the dependences of the condensation and the critical temperature/critical chemical potential on the inhomogeneity in these two different spacetimes. By exploring the dynamics of the normal phase through the scalar field perturbation, we argue that the pair susceptibility and the conductivity can be possible phenomenological indications to disclose the property of inhomogeneity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…5 Holographic superconductors with spatially modulated orders have been studied in a number of setups, starting with [19], in which striped modulations were sourced by a periodic chemical potential, with many generalizations in the literature since then, e.g. [20][21][22][23][24]. A study of backreaction by adding a lattice in the form of a periodic potential was reported in [25].…”
Section: Jhep08(2017)081mentioning
confidence: 99%
“…5 Holographic superconductors with spatially modulated orders have been studied in a number of setups, starting with [19], in which striped modulations were sourced by a periodic chemical potential, with many generalizations in the literature since then, e.g. [20][21][22][23][24]. A study of backreaction by adding a lattice in the form of a periodic potential was reported in [25].…”
Section: Jhep08(2017)081mentioning
confidence: 99%
“…An accurate realization of thermoelectric conductivities in real condensed matter systems requires us to include mechanisms for momentum dissipation. Recently, it was suggested to introduce momentum relaxation in holography by exploiting spatially dependent sources for scalar operators or using the massive gravity [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The reduction action for the anisotropic black brane used in this paper, is the Einstein-Maxwell dilaton-axion theory.…”
Section: Introductionmentioning
confidence: 99%
“…To make our life easier, in what follows we shall not touch upon the striped phase structure as in [38,39], but restrict ourselves solely on the homogeneous phase structure of our model, which can be implemented by the homogeneous ansatz for the bulk matter fields as…”
Section: Holographic Modelmentioning
confidence: 99%